Curcumin improves age-related and surgically induced osteoarthritis by promoting autophagy in mice. Issue 4 (3rd July 2018) - Zhang, Guowang; Cao, Jiaqing; Yang, Erzhu; Liang, Bo; Ding, Jianing; Liang, Jiaming; Xu, Jianguang
Abstract : Reduced autophagy has been implied in chondrocyte death and osteoarthritis. Curcumin (Cur) owns therapeutic effect against osteoarthritis (OA) and enhances autophagy in various tumor cells. Whether the cartilage protection of curcumin is associated with autophagy promotion and the potential signaling pathway involved remains unclear. The present study aimed to investigate the role of autophagy in the anti-OA activity of curcumin using spontaneous and surgically induced OA mice model. Spontaneous and surgically induced OA mice model was established and treated with Cur. Articular cartilage destruction and proteoglycan loss were scored through Safranin O/Fast green staining. Apoptotic cell death was detected with TUNEL (terminal deoxynucleotidyl transferase-mediated dTUP-biotin nick end labeling assay) staining and Western blot for caspase-3, Bcl-2 associated X protein (Bax), and Bcl-2 (B-cell lymphoma-2). Light chain 3 (LC3) immunohistochemistry was used to evaluate autophagy. In vitro, primary chondrocytes were treated with interleukin 1 beta (IL-1β) and Cur. Autophagy was inhibited using 3-methyladenine. Apoptosis and autophagy were detected using flow cytometry and Western blotting assay. Curcumin treatment enhanced autophagy, reduced apoptosis, and cartilage loss in both OA models. In vitro, curcumin treatment improved IL-1β induced autophagy inhibition, cell viability decrease, and apoptosis. Mechanistically, in vivo studies suggested curcumin promoted autophagy through regulating Akt/mTOR pathway. In conclusion, our results demonstrate that curcumin-induced autophagy via Akt/mTOR signaling pathway contributes to the anti-OA effect of curcumin.